Пенітенціарна система Російської імперії у дореформений період (на прикладі українських губерній) - Левчук, І.; Levchuk, І. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті аналізуються історично-правові аспекти функціонування пенітенціарної системи Російської імперії у дореформений період. Емпіричним підґрунтям нам слугували матеріали, що територіально обмежуються українськими губерніями. З’ясовано організаційні аспекти діяльності закладів пенітенціарії на українських землях, що входили до складу Російської імперії. Зроблено висновок щодо невідповідності дореформеного періоду системи виконання покарань тогочасним загальноєвропейським уявленням про злочин і покарання та її вплив на подальші реформи 1860-х років. The article analyzes the historical and legal aspects of penitentiary system functioning in Russian Empire in pre-reforming period. The study of the problem is based on the materials concerning only the territories of Ukrainian provinces. It has been found out that pre-reforming period in the development of the prison system in the Russian Empire is characterized by systematization of scattered legal regulations. Administrating of prisons was characterized by radically opposite processes. There was no central administration system and the prisons appeared to be subordinated to different departments. The article offers insights into the organizational aspects of the penitentiary institutions on the territory of Ukrainian lands in Russian Empire. The author draws conclusions about non-compliance of pre-reforming penitentiary system of Russia with Western ideas about crime and punishment and European penal systems and its impact on further reforms in 1860-ies. As a result the processes of formation of new approaches to the correction of criminals and humane attitude towards them started in Russia under the influence of Western ideas; much attention was paid to centralization of prisons administration. The aforementioned factors created preconditions and factual grounds for introducing reforms in penal system aimed at humanization of criminal punishment and reforming prison administration.
Penitentiary System in Russian Empire in Pre-reforming Period (Case Study of Ukrainian Provinces).
Keywords: пенітенціарна система; виконання покарань; Російська імперія; українські губернії; система закладів виконання покарань; penal system; enforcement of sentences; Russian Empire; Ukrainian provinces; system of the penitentiary institutions